GET TO KNOW WHAT HAPPEN THROUGH SOCIAL MEDIA ANALYSIS USING BRAND24 - Septiasari, Abellia; Rizqi Amelia, Aulya; Dyah Larasati, Annita; Hartanto, Jonathan Chris; Martsha Buana, Salsabilla Ayundha; Mawardi, Viny Christanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
In utilising social media as a means of product promotion, a brand can collaborate with an influencer and/or famous artist to market the brand's products. The use of analytic tools can make a business or brand effective by looking at consumer communication, whether the brand's marketing has a good or bad impact on its target market. This social media analytics activity is concerned with collecting data from relevant social media, analysing the data collected, and disseminating the findings accordingly to support their business activities. The purpose of this seminar is to assist partners in increasing their knowledge about social media analysis and social media analytics using tools, also for partners to have the ability to make decisions based on the results of analyses on social media. After the seminar, the partners are expected to reflect on how the use of social media has changed the way they communicate, interact with others, and access information. This can be a strong basis for personal reflection on the positive and negative impacts of social media in their lives.